Investigation of the Basic Steps in the Chromosome Conformation Capture Procedure - Bylino, Oleg V.; Ibragimov, Airat N.; Pravednikova, Anna E.; Shidlovskii, Yulii V. (Frontiers in Genetics, 2021)
A constellation of chromosome conformation capture methods (С-methods) are an important tool for biochemical analysis of the spatial interactions between DNA regions that are separated in the primary sequence. All these methods are based on the long sequence of basic steps of treating cells, nuclei, chromatin, and finally DNA, thus representing a significant technical challenge. Here, we present an in-depth study of the basic steps in the chromatin conformation capture procedure (3С), which was performed using Drosophila Schneider 2 cells as a model. We investigated the steps of cell lysis, nuclei washing, nucleoplasm extraction, chromatin treatment with SDS/Triton X-100, restriction enzyme digestion, chromatin ligation, reversion of cross-links, DNA extraction, treatment of a 3C library with RNases, and purification of the 3C library. Several options were studied, and optimal conditions were found. Our work contributes to the understanding of the 3C basic steps and provides a useful guide to the 3C procedure.